Investigation on the effect of ulinastatin on the apoptosis of vascular smooth muscle cells in rats with aortic dissection based on the Sirt1/FoxO3a pathway - Peng, Xiaopeng; Yuan, Haoyao; Guo, Yuliang; Chen, Qiming; Cao, Weidong (Cellular and Molecular Biology, 2023)
This study aimed to investigate the effects of ulinastatin on the apoptosis and (Sirt1/FoxO3a) pathway of vascular smooth muscle cells (VSMC) in aortic dissection (AD) rats. For this purpose a rat model of aortic dissection (AD) was constructed by giving drinking water containing 0.08% β-aminopropionitrile (BAPN) to rats, HE staining was used to observe the pathological changes of the aorta in AD rats; the diseased blood vessels of AD rats were taken for primary culture and passage of VSMCs, the morphology of VSMCs was observed, and VSMCs were identify with immunofluorescence staining; VSMCs were treated with culture media containing 0, 1000, 2000, 3000, 4000, 5000, 6000, 7000 U/mL ulinastatin, and MTT kit was used to determine the effect of ulinastatin on VSMC proliferation in AD rats; the VSMC of AD rats were divided into blank group (normal culture), ulinastatin group (medium containing 5000 U/mL ulinastatin), Sirt1 inhibitor group (medium containing 1 μmol/L EX527), ulinastatin + Sirt1 inhibitor group (medium containing 5000 U/mL ulinastatin, 1 μmol/L EX527), flow cytometry was used to detect the VSMC apoptosis in each group, WB was used to detect the expression of VSMC apoptosis-related proteins and Sirt1/FoxO3a pathway-related proteins in each group. Findings suggested that the aortic wall of AD rats was thickened, and the dissection false cavity appeared; VSMC mostly presented different shapes such as triangles and stars, the immunofluorescence staining results showed that α-SMA was arranged in the cytoplasm in the form of myofilaments, showing green fluorescence, and the nucleus showed blue fluorescence, and the rate of positive cells was more than 95%; various doses of ulinastatin had a certain inhibitory effect on the proliferation of VSMC, and 5000 U/mL ulinastatin had a higher proliferation inhibition rate; compared with the blank group, the VSMC apoptosis rate, Caspase-3, Bax protein, Sirt1/FoxO3a pathway related protein expression in the ulinastatin group were significantly increased, and the Bcl-2 protein expression was significantly decreased (P<0.05), the VSMC apoptosis rate, Caspase-3, Bax protein, Sirt1/FoxO3a pathway related protein expression in the Sirt1 inhibitor group were significantly decreased, and the Bcl-2 protein expression was significantly increased (P<0.05); compared with the ulinastatin group, the VSMC apoptosis rate, Caspase-3, Bax protein, Sirt1/FoxO3a pathway related protein expression in the ulinastatin + Sirt1 inhibitor group were significantly decreased, and the Bcl-2 protein expression was significantly increased (P<0.05). It was concluded that ulinastatin can inhibit the proliferation of VSMCs in AD rats and promote their apoptosis, which may be achieved by activating the Sirt1/FoxO3a pathway.